Exploring the Relationship Between Business Strategy and Project Management Tools and Techniques: A Case Study in the Marketing Industry - Herzing, Ian M. (International Review of Management and Marketing, 2024)
Project management tools and techniques (PMTT) have been understudied in marketing. This research explored PMTT alignment with business strategy in a marketing agency via a qualitative case study. Data collection involved a focus group, questionnaires, and interviews examining how PMTT influence schedules, quality, budgets, and clients. Analysis revealed selection and use of PMTT is driven by strategic emphasis on agility, cost- efficiency, and client needs. Findings confirmed PMTT’s role in meeting timelines and budgets while ensuring quality. A proposed matrix connects PMTT with strategy. Though a single case, the study provides templates to match PM toolkits to business strategy. Further research can build on the strategic and contingency insights regarding adaptable PMTT use. Overall, findings advance practical relevance through strategy-linked PMTT customization suited to this project-focused creative context.